2020
DOI: 10.1038/s41422-020-00408-2
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation by SARS-CoV-2 nucleocapsid protein and RNA

Abstract: Dear Editor, The COVID-19 pandemic worldwide is caused by a novel coronavirus SARS-CoV-2 (the severe acute respiratory syndrome coronavirus 2). 1 After viral invasion into the host cells, the~30 kb viral genome RNA injected is translated into structural and nonstructural proteins to replicate viral genome and assemble more viral particles. Many copies of nucleocapsid (N) protein can bind to viral genome RNA and pack it into~100 nm particles, assisting membrane (M) and envelope (E) proteins to efficiently assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
161
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(174 citation statements)
references
References 13 publications
13
161
0
Order By: Relevance
“…However, studies have shown that SARS-CoV N protein disturbed the IFN-β levels [ 22 , 23 , 24 ], and recent studies have suggested that SARS-CoV-2 caused a delayed interferon response [ 6 ]. Indeed, SARS-CoV-2 N protein plays a key role in viral genome packaging and the replication cycle [ 38 , 39 ]. Here, we explored the relationship between SARS-CoV-2 N protein and IFN-β response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that SARS-CoV N protein disturbed the IFN-β levels [ 22 , 23 , 24 ], and recent studies have suggested that SARS-CoV-2 caused a delayed interferon response [ 6 ]. Indeed, SARS-CoV-2 N protein plays a key role in viral genome packaging and the replication cycle [ 38 , 39 ]. Here, we explored the relationship between SARS-CoV-2 N protein and IFN-β response.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that SARS-CoV-2 N protein plays a key role in viral genome packaging [ 38 , 39 ]. Indeed, RIG-I is a key sensor of RNA virus infection, which mediates the activation of type I interferons and other genes that collectively establish an antiviral host response.…”
Section: Resultsmentioning
confidence: 99%
“…2A) [20][21][22]. Such organization allows for a vast conformational change, which in combination with positively charged surfaces [23], facilitates nucleic acid binding [24]. Indeed, the crystal structure of the N-terminal domain (NTD) reveals an RNA binding groove [25][26][27], while crystal structures of the Cterminal domain (CTD) show a highly interlaced dimer with additional nucleic acid binding capacity [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we would like to point out that while we were in the process of preparing this manuscript, a paper was published showing that N protein phase separated with RNA and that this process could be enhanced by Zn 2+ 14 . Similar to these findings, we also demonstrated that N protein phase separation was triggered by HeLa cell total RNAs in a dose-dependent manner.…”
mentioning
confidence: 99%